Digital Technology Development and Income Inequality in Indonesia: Using System GMM Model - Sugeng Setyadi; Lili Indriyani; Rizal syaifudin (EKO-REGIONAL, 2023)
This study aimed to analyze the importance of information and communication technology (ICT) for economic development. ICT development has been widely studied and well understood, but its impact on income inequality is less well documented. Therefore, this study used a panel data set in 34 provinces in Indonesia during 2013-2020 to examine the impact of ICT development on income inequality. The econometric Generalized Method of Moments (GMM) with the estimation model of the System GMM showed that higher ICT development (Information and Communication Technology Development Index) reduces income inequality (Gini Ratio). This implies that ICT development does not contribute to exacerbating income inequality. However, it could play a role in mitigating and reducing income inequality in Indonesia. Socio-economic and political factors are also important in reducing income inequality. Therefore, redistribution policies and government spending are crucial to reducing income inequality due to ICT development. These policies must be adapted to the needs of each region for ICT development.Keywords: ICT Development, Income Inequality, Socio-Economic and Political Factors, GMM Model.